Novel technique for high-quality microstructuring with excimer lasers - Roth, Stephan; Geiger, Manfred (Proceedings of SPIE, 2000)
Laser micromachining has become increasingly established in many microsystems applications during the past years. These new fields occasion higher demands on the quality of micromachined devices combined with high resolution and working velocity. Due to the disadvantages of conventional excimer laser processing, a novel technique is required to meet these demands. The main problems of conventional excimer laser machining are the redeposition of ablated material on the irradiated work piece and the formation of a strong melting phase especially for metals. These difficulties greatly reduce the applicability of excimer laser material processing for manufacturing microsystems technology components. By applying a thin water film to the substrate surface, the redeposition of ablated material can be completely avoided, which results in a better quality of the microstructures. Usage of a water film, however, has proved to lead to a marked reduction of the ablation rate for the examined materials - ceramics and stainless steel. Therefore, one of the objectives of future research will be to raise the ablation rate in order to render excimer laser processing more interesting economically. Adding alcoholic additives, among others, has improved the wetting of the liquid films on the surface. The effect of the modified chemical composition of the liquid on ablation rate and structure quality for various materials is presented here.
LFT Import::2019-07-15 (799)